2016
DOI: 10.1007/s11748-016-0672-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo malignancy after lung transplantation in Japan

Abstract: This is the first national survey of the incidence of de novo malignancy after lung transplantation in Japan. The incidence was 10.1 % and post-transplant lymphoproliferative disorder was the most common malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There are few articles related to lung transplantation, and only one of which meets our screening conditions was selected whose title is "De Novo Malignancy after Lung Transplantation in Japan" [28]. It summarizes 179 lung transplantation operations performed in 7 institutions in Japan from 2001 to 2010, of which 18 recipients (10.1%) developed new malignancies.…”
Section: Morbidity Of Carcinoma Of Postheart Transplantationmentioning
confidence: 99%
“…There are few articles related to lung transplantation, and only one of which meets our screening conditions was selected whose title is "De Novo Malignancy after Lung Transplantation in Japan" [28]. It summarizes 179 lung transplantation operations performed in 7 institutions in Japan from 2001 to 2010, of which 18 recipients (10.1%) developed new malignancies.…”
Section: Morbidity Of Carcinoma Of Postheart Transplantationmentioning
confidence: 99%
“…Although two recent Japanese studies revealed that de novo malignancy occured at an incidence of 10.1% and post transplant lymphoproliferative disorder was the most common malignancy after lung transplantation, regardless the source of organ was from living donor or cadaver [18, 19], the cancer risk among Asian organ transplant recipients has been limited. However, Taiwan launched the National Health Insurance (NHI) Program in 1995, with nationwide coverage.…”
Section: Introductionmentioning
confidence: 99%
“…We report an incidence of 7.6% similar to others studies (5.2% to 17%). 10 However, this incidence may even be underestimated, as the study included all LT patients with a very short post-LT follow-up. As described by ISHLT, the most common malignancies in this series were skin cancer and PTLD.…”
Section: Discussionmentioning
confidence: 99%